Perancangan Strategi Sistem Informasi di Era Digital: Sebuah Kajian Systematic Literature Review - Waspodo, Bayu; Ramadhanti, An Nisa; Latifah, Putri (Progresif: Jurnal Ilmiah Komputer, 2026)
The rapid development of digital technology requires organizations to transform information systems from administrative tools into strategic assets that support decision-making, innovation, and competitive advantage. This study aims to examine information system strategy design in the digital era. A Systematic Literature Review (SLR) method was applied, including identification, selection, evaluation, and synthesis of studies from Google Scholar, ScienceDirect, Scopus, and IEEE Xplore (2020–2025). A total of 25 relevant articles were analyzed. The findings indicate that Ward and Peppard, Enterprise Architecture (TOGAF and Zachman), and agile strategic planning are widely used to align business and IT strategies, improve operational efficiency, and enhance organizational adaptability. However, challenges remain, including limited human resource capabilities, resistance to change, and increasing digital complexity.Keywords: Information systems; Strategic planning; Digital transformation; Systematic Literature Review.AbstrakPerkembangan teknologi digital menuntut organisasi mentransformasikan perencanaan dan pengelolaan sistem informasi dari fungsi administratif menjadi strategis untuk mendukung keputusan, inovasi, dan keunggulan kompetitif. Penelitian ini bertujuan mengkaji perancangan strategi sistem informasi di era digital. Metode yang digunakan adalah Systematic Literature Review (SLR) dengan tahapan identifikasi, seleksi, evaluasi, dan sintesis literatur dari Google Scholar, ScienceDirect, Scopus, dan IEEE Xplore periode 2020–2025. Sebanyak 25 artikel terpilih dianalisis. Hasil menunjukkan bahwa pendekatan Ward and Peppard, Enterprise Architecture (TOGAF dan Zachman), serta agile strategic planning efektif dalam menyelaraskan strategi bisnis dan teknologi, meningkatkan efisiensi, serta mendukung inovasi organisasi. Namun, implementasi masih menghadapi tantangan berupa keterbatasan sumber daya manusia, resistensi perubahan, dan kompleksitas lingkungan digitalKata kunci: Sistem informasi; Perencanaan strategis; Transformasi digital; Systematic Literature Review.